Contextual and Interactional Approaches to Advancing Leadership and Entrepreneurship Research. (12th June 2020) - Pollack, Jeffrey M.; Carr, Jon C.; Corbett, Andrew C.; Hoyt, Crystal L.; Kellermanns, Franz W.; Kirkman, Bradley L.; Post, Corinne
Abstract: In this introductory article for the special issue of Journal of Management Studies, entitled 'Leading Entrepreneurial Ventures: Individual and Team‐Based Perspectives', we leverage insights in the extant literature as well as those insights developed by the authors of the four articles published in response to our call for papers. Overall, we explore multiple nuanced questions with regards to research on entrepreneurship, research on leadership, and their intersection. Our goal is to begin to help guide research on entrepreneurship and leadership, and their intersection, for the next decade.